Genetic Architectures of Quantitative Variation in RNA Editing Pathways. Issue 2 (24th November 2015) - Gu, Tongjun; Gatti, Daniel M; Srivastava, Anuj; Snyder, Elizabeth M; Raghupathy, Narayanan; Simecek, Petr; Svenson, Karen L; Dotu, Ivan; Chuang, Jeffrey H; Keller, Mark P; Attie, Alan D; Braun, Robert E; et al.
Abstract: RNA editing refers to post-transcriptional processes that alter the base sequence of RNA. Recently, hundreds of new RNA editing targets have been reported. However, the mechanisms that determine the specificity and degree of editing are not well understood. We examined quantitative variation of site-specific editing in a genetically diverse multiparent population, Diversity Outbred mice, and mapped polymorphic loci that alter editing ratios globally for C-to-U editing and at specific sites for A-to-I editing. An allelic series in the C-to-U editing enzyme Apobec1 influences the editing efficiency of Apob and 58 additional C-to-U editing targets. We identified 49 A-to-I editing sites with polymorphisms in the edited transcript that alter editing efficiency. In contrast to the shared genetic control of C-to-U editing, most of the variable A-to-I editing sites were determined by local nucleotide polymorphisms in proximity to the editing site in the RNA secondary structure. Our results indicate that RNA editing is a quantitative trait subject to genetic variation and that evolutionary constraints have given rise to distinct genetic architectures in the two canonical types of RNA editing.